The REQUIREMENTS FOR VEGETATIVE GROWTH OF HOHENBUEHELIA MYXOTRICHA AND ITS ANTIMYCOTIC ACTIVITY: GROWTH AND ANTIMYCOTIC ACTIVITY OF HOHENBUEHELIA MYXOTRICHA - Barshteyn, Victor (Polish Journal of Natural Sciences, 2022)
Biometric characteristics of the hyphae and micromorphological features of Hohenbuehelia myxotricha mycelia, such as clamps, hyphal loops, crystals were observed by light and electron microscopy. The basic requirements for H. myxotricha growth and acquisition of antimycotic activity have been investigated. The highest mycelial growth (18.2 mm/day) of H. myxotricha was observed on beer wort agar medium. Suitable conditions for maximal H. myxotricha mycelia production were found after 14 days of liquid static cultivation at 25 °C, pH 4.5, 30 g/L of glucose, and 2 g/L of yeast extract. The inhibitory effect of H. myxotricha was evaluated against Aspergillus niger, Issatchenkia orientalis, and Candida albicans strains. The optimal period for A. niger growth inhibition was 14 days while 21 days of H. myxotricha cultivation was more appropriated for Saccharomycetaceae fungi growth inhibitions. The most suitable for promotion of antimycotic metabolites against all tested pathogenic fungi were glucose and yeast extract. Compliance with established suitable cultivation conditions will allow for obtaining the maximum mycelia of H. myxotricha and its antimycotic metabolites that can be potential useful for medicinal purposes.